The impact of perceived lack of support provided by health and social care services to caregivers of people with motor neuron disease. - Peters, M; Fitzpatrick, R; Doll, H; Playford, E; Jenkinson, C (2012)
Our objective was to investigate the relationship between support by health and social care services and caregiver well-being. A survey, including a generic health status measure (SF-12), a disease-specific measure for patients (ALSAQ-40), the Carer Strain Index (CSI) for caregivers and questions on experiences of health and social care services, was sent to patient members of the MND Association (UK) and their caregivers. A single 'problem score' was calculated from the experience questions and the relationship between the problem score with caregiver and patient well-being was analysed. Most caregivers reported at least one problem with support from services. The most common problems were services not valuing caregivers' experiences, and caregivers not feeling sufficiently involved in planning care. The problem score significantly increased with increasing caregiver strain and worsening mental health. The problem score was also increased as patient well-being decreased. The results suggest that caregiver strain was higher and mental health lower as the number of problems reported increased. A higher perceived lack of caregiver support was also related to a decrease in patient well-being, suggesting that caregivers' needs increase as the disease progresses. This emphasizes the importance of MND caregivers being appropriately supported by health and social care services in their caregiving role.